Efektivitas Pembelajaran Berbasis Web Wolfram Alpha Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Pada Materi Fungsi Kuadrat Di Kelas X SMK Swasta Imelda Medan T.A 2025/2026 - simangunsong, angginita; Hutauruk, Agusmanto JB; Simbolon, Lolyta Damora (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to determine the effectiveness of Wolfram Alpha-based web learning on students’ mathematical problem-solving skills in quadratic functions in Grade X at Imelda Private Vocational High School, Medan, Academic Year 2025/2026. This is a pre-test post-test control groupdesign study with the research population consisting of students in Grade X at Imelda Private Vocational High School, Medan. The research sample was selected using simple random sampling, resulting in the experimental class MP1 and the control class X-TKJ4. After being subjected to different treatments, the data were analyzed using inferential and descriptive analysis. The results of the analysis showed that the data on conceptual understanding met the prerequisite tests and were normally distributed, homogeneous, and linear. The t-test (α = 0.05) revealed a significant difference between the experimental and control classes. The results of the study showed that students’ mathematical problem-solving skills met the effectiveness indicators, leading to the conclusion that web-based learning is effective in enhancing students’ mathematical problem-solving skills.